A new matheuristic approach for the multi-depot vehicle routing problem with inter-depot routes - Ramos, T. R. P.; Gomes, M. I.; Barbosa-Póvoa, A. P. (OR Spectrum, 2020)
The multi-depot vehicle routing problem with inter-depot routes is studied in this paper, where vehicles may reset their capacity at any depot during the working day. Due to the complexity of this problem, exact approaches are limited to small-size applications. In order to overcome this limitation, we propose a matheuristic which integrates a mixed integer linear programming formulation with a set of relax-and-fix strategies. This solution approach is shown to be very efficient, and for the first time, large-size benchmarking instances are solved.